Pemanfaatan perjanjian perdagangan internasional melalui pemberdayaan UMKM oleh FTA Center Jakarta periode 2018-2019 - Surjadi Basuki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Indonesia is significantly intensifying the international-trade agreement with several strategic trade partners. Some said that the agreement would lead to the increasing flow of imported goods to Indonesia. Free Trade Agreement (FTA) Center Jakarta indeed aimed at empowering Indonesian small and medium enterprises (SMEs) to enjoy the benefits of more open export opportunities. Through coaching clinic and personal consultation method, the SMEs acquire knowledge on available export opportunities and training to improve the skills that suitable to their needs. Within a year of the empowerment program, around 100 SMEs have been reaching positive achievements that increase their confidences in penetrating export market or expanding their export activities.